The Impact of Self-assessment System On Compliance Levels of Small And Medium Enterprises Case Study van Sales Company - Wadesango; Mutema; Mhaka (Allied Business Academies, 2021)
Introduction The study aimed at assessing the effect of self-assessment systems on the compliance levels of SME’s. Various fiscal reforms aimed at broadening the tax base have been successfully introduced by Zimra and one of them is the Self-Assessment of Income Tax. Notable authors such as (Okello, 2014; Appah, 2013; Farik, 2016) are of the view that voluntary tax compliance is best achieved through a system of self-assessment. They also agree that the self- assessment system is efficient in administering cost reduction and they came up with a key assumption that self-assessment is based on the trustworthy of the tax payer for they know the profits they are making in their business.